1973
DOI: 10.1139/f73-054
|View full text |Cite
|
Sign up to set email alerts
|

Extension of Shelf-Life of Indian Mackerel (Rastrelliger kanagurta) by Irradiation

Abstract: A dose of 150 krad was optimum for extending refrigerated (0–2 C) shelf-life of fresh Indian mackerel (Rastrelliger kanagurta). This dose extended the shelf-life to 25–30 days from 10–12 days without inducing undesirable changes in the organoleptic qualities. Vacuum-packaging affected the appearance of the irradiated product by drawing out muscle fluids during storage. Samples irradiated aerobically did not become rancid and were acceptable to a taste panel. Storage of fish in ice beyond 5 days before irradiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1978
1978
1999
1999

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…Preirradiation ice storage beyond 5 days significantly reduced postirradiation storage life of the fish. 69,299,303 The radiation treatment had no significant effect on physicochemical and other qualities. 298,301 The data are summarized in Table 6.…”
Section: A Radurizationmentioning
confidence: 95%
See 4 more Smart Citations
“…Preirradiation ice storage beyond 5 days significantly reduced postirradiation storage life of the fish. 69,299,303 The radiation treatment had no significant effect on physicochemical and other qualities. 298,301 The data are summarized in Table 6.…”
Section: A Radurizationmentioning
confidence: 95%
“…Thiobarbituric acid (TBA) values of nonirradiated and irradiated (0.05 kGy) fish fillets were not significantly different, although at 1 kGy some lipid oxidation in terms of high TBA value was noticed. 171,173,261 Venugopal et al 303 reported that rancidity was not significant in air-packaged Indian mackerel. Although there was initial increase, the TBA value of irradiated fish decreased during storage.…”
Section: Lipidsmentioning
confidence: 99%
See 3 more Smart Citations